2021
DOI: 10.1186/s40981-021-00424-0
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam anesthesia for cardiac surgery with cardiopulmonary bypass: a case report

Abstract: Background Remimazolam has less cardiovascular depressant effects than propofol in non-cardiac surgical patients. However, the efficacy and safety of remimazolam in cardiac surgery with cardiopulmonary bypass (CPB) have not been reported. We present a case of successful anesthetic management using remimazolam in cardiac surgery with CPB. Case presentation A 76-year-old female was scheduled for mitral valve repair, tricuspid annuloplasty, maze proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…In addition, remimazolam can be used for patients with a history of egg allergy. However, there has been only one report on the effects of remimazolam on MEP response [10]. Our case report provides further evidence regarding the use of remimazolam for MEP monitoring.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, remimazolam can be used for patients with a history of egg allergy. However, there has been only one report on the effects of remimazolam on MEP response [10]. Our case report provides further evidence regarding the use of remimazolam for MEP monitoring.…”
Section: Discussionsupporting
confidence: 65%
“…The amplitude of MEPs decreased in our patient, and weakness of the foot was confirmed after anesthesia because of the rapid elimination of remimazolam. Remimazolam has some advantages including no vascular pain at administration and less circulatory depression [10]. In addition, remimazolam can be used for patients with a history of egg allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Even 6 mg/kg/h remimazolam was successful at inducing anaesthesia in all critically ill patients in ASA class III or higher [ 9 ]. One study reported that general anaesthesia for cardiac surgery was induced with 6 mg/kg/h remimazolam [ 10 ]. We selected 6 mg/kg/h as the induction dose based on the patient’s cardiac condition.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, further study is required on the use of remimazolam in craniotomy to understand better the risk/ benefit balance. Successful use of remimazolam has been described in spine surgery incorporating motor evoked potential monitoring (Kondo et al, 2020), thyroid surgery with neuromonitoring (Hayamizu et al, 2021), and cardiac surgery with cardiopulmonary bypass (Saito et al, 2021). Remimazolam's successful use in high-risk patients, including endoscopic retrograde cholangiopancreatography in a patient with impaired respiratory function due to myotonic dystrophy (Fukuda et al, 2021), MitraClip implantation in a patient with advanced heart failure (Satoh et al, 2021), and cochlear implant in a patient with mitochondrial myopathy (Suzuki et al, 2021) has been published.…”
Section: Case Reportsmentioning
confidence: 99%